Pendekatan Fun Learning Dalam Meningkatkan Interaksi Sosial Anak Di Paud Insklusi - Nadia Aliyatuz Zulfa; Bono Setyo; Nurita sari (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to explore the implementation of the Fun Learning approach in improving children's social interaction in Insan Kamil Tuban Kindergarten as an inclusive PAUD. The research method used is qualitative with a case study approach, involving observation, in-depth interviews, and documentation. The results of the study show that the Fun Learning approach through collaborative activities, such as role-playing and creative arts, is effective in increasing the frequency, quality, and courage of children's social interactions. Supporting factors include teacher commitment and adequate facilities, while barriers include differences in children's abilities and limited resources. In conclusion, Fun Learning has been proven to be able to create inclusive learning and improve children's social skills, although advanced training is required for teachers.